The puzzle of populism in Iran's electoral politics. Issue 6 (18th August 2019) - Raisi, Alireza
ABSTRACT: The article examines the impact of an unsettled electoral market and evolving political predispositions on the rise and fall of populism in Iran. The article argues that the absence of a polarized electoral contest between reformists and conservatives paved the way for the victory of the populist candidate in the 2005 presidential election in Iran, while the deep economic recession resulting from conservative administration policies created a long-term political experience which influenced voters and led to the victory of the pragmatist candidate in the 2013 and 2017 elections. Quantitative analysis indicates that in the 2005 election, the struggle between conservatives and reformists did not impact the competition between candidates, and consequently depoliticized attitudes, for example distributive demands, ideology, and anti-ruling elite sentiment gained significance, whereas polarization between conservatives and a coalition of reformists and pragmatists enhanced the role of partisanship and triggered the fall of populism in the 2013 election.